On Verbless Clauses in Akkadian - Huehnergard, John
ersch. 1987; Types of Predicate - Word Order - Predicative and Non-predicative Forms - Existential Clauses - Clauses with a Copula Pronoun - The Copula Pronoun in Western Peripheral Texts